Mobile Wireless Middleware, Operating Systems, and Applications 4th International ICST Conference, Mobilware 2011, London, UK, June 22-24, 2011, Revised Selected Papers - Venkatasubramanian, Nalini; Getov, Vladimir; Steglich, Stephan; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2012)
This book constitutes the thoroughly refereed proceedings of the 4th International Conference on Mobile Wireless Middleware, Operating Systems, and Applications, Mobilware 2011, held in London, UK, in June 2011. The 21 revised full papers presented were carefully reviewed and selected from numerous contributions. The papers are organized in topical sections on mobile systems in education, SOC for mobile Apps (SOC), networking platforms (NW), mobile execution frameworks (MFW), mobile cloud (MC) and distributed execution, and mobile sensor networks.
Keywords: Computer science; Computer Communication Networks; Software engineering; Information storage and retrieval systems; Artificial intelligence; Computer Science; Computer Communication Networks; Information Systems Applications (incl. Internet).; User Interfaces and Human Computer Interaction; Software Engineering; Information Storage and Retrieval; Artificial Intelligence (incl. Robotics).